Blood types and Cancer Risk: A Comprehensive Analysis of ABO/Rh Association with Colorectal Cancer - Yılmaz, Mustafa; Benli, Sami; Özcan, Cumhur; Çolak, Tahsin (Asian Pacific Journal of Cancer Care, 2025)
Background: The association between ABO/Rh blood groups and colorectal cancer (CRC) remains inconsistent. This study evaluates their impact on CRC risk and prognosis. Methods: A retrospective case-control study of 1,687 CRC patients and 1,836 matched controls (2010–2024) analyzed blood group distributions, tumor characteristics, and survival using chi-square tests and logistic regression (p < 0.05). Results: The AB Rh (+) phenotype was significantly more prevalent in CRC patients than controls (p = 0.032). The AB blood group was associated with higher risk (OR: 3.56; 95% CI: 1.77–7.15), aggressive tumor features (advanced T stage, metastasis and increased anastomotic leakage), and shorter median survival (30.5 vs. 40.0 months for O group; p < 0.05). Conclusions: AB blood group is linked to increased CRC risk and poorer prognosis, suggesting its potential as a biomarker for risk stratification.